Epidemiology of Childhood Blindness and Low Vision in Kinshasa–democratic Republic of the Congo. (2nd January 2020) - Kilangalanga, Ngoy Janvier; Nsiangani, Lusambo Nadine; Dilu, Ahuka Angele; Moanda, Kapopo Astrid; Ilunga, Muleya Josette; Makwanga, Mankiew Emile; Stahnke, Thomas; Guthoff, Rudolf
ABSTRACT: Purpose : To determine the magnitude and causes of blindness and low vision in children in Kinshasa. Methods : A study was conducted to carry out a survey in 96 health areas in Kinshasa city. Children aged less than 16 years old with supposed visual problems (Visual acuity < 6/18) were identified by volunteers and surveyors in households and were thereafter examined by two ophthalmologists. Prevalence and causes of blindness and low vision were determined. For each child, anatomic sites of abnormality, etiologic factors and avoidable causes responsible for visual impairment were considered. Results : Thirty-six children with bilateral visual impairment were identified, including 10 cases of blindness and 26 cases of low vision. The prevalence of blindness and low vision was, respectively, 0.08% [95% CI 0.04–0.14] and 0.19% [95% CI 0.13–0.28].Optic nerve and whole globe were the main anatomical sites responsible for blindness in, respectively, in 30% and 20%. Optic nerve atrophy and glaucoma were the leading causes of childhood blindness. The globe apparently normal (50%), uvea (12%) and cornea (12%) were the most common anatomic site responsible for low vision with refractive errors (42%) and uveitis (12%) as the main causes. Childhood and hereditary factors accounted for, respectively, 16.7% and 13.9% of low vision cases. Visual impairment was due to avoidable causes in 69.4% of children. Conclusion : Damage to the optic nerve and refractive errors were respectively the maincauses of blindness and low vision among children in Kinshasa.